Postgraduate students motivation for mooc enrollment - Jais J.; Chen S.D.; Rahim R.E.A.; Md Din N. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This study was conducted in order to identify the motivational factors for student in pursuing Massive Open Online Courses (MOOC). The respondents of this study consisted of 38 postgraduate students studying in Universiti Tenaga Nasional (UNITEN). The results showed that students are motivated to enroll MOOC which are offered by prestigious universities. Students curiosity to learn the content of MOOC is also another important factor. The study also indicated that students are motivated to pursue MOOC which are supplementary to the content of classes offered by other institutions. BEIESP.